A closed-form expression of effective permittivity with spherically symmetric function for honeycomb structure. (13th August 2021) - Li, Shilei; Wan, Guobin; Fu, Bin; Liu, Yunzhe; Wang, Nan
Abstract: A novel closed-form expression for predicting the equivalent electromagnetic parameters of the honeycomb structure is proposed. It is obtained by approximating the correlation terms in the derivation of the strong fluctuation theory with the integral of the spherically symmetric function. Through several simulation examples, the calculation results of the formula are compared with the results of several traditional extraction methods and compared with the existing experimental data. Comparison of the extraction results of the formula with the simulation results and the experimental data shows good agreement, which proves the feasibility of the extraction expression, and this method does not require simulation as a prerequisite and can shorten the time for optimizing the design of the honeycomb absorbing structure.